2011
DOI: 10.1051/0004-6361/201116618
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic signature of an intermediate-mass black hole in the globular cluster NGC 6388

Abstract: Context. Intermediate-mass black holes (IMBHs) are of interest in a wide range of astrophysical fields. In particular, the possibility of finding them at the centers of globular clusters has recently drawn attention. IMBHs became detectable since the quality of observational data sets, particularly those obtained with HST and with high resolution ground based spectrographs, advanced to the point where it is possible to measure velocity dispersions at a spatial resolution comparable to the size of the gravitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(157 citation statements)
references
References 55 publications
9
145
3
Order By: Relevance
“…The effective velocity dispersion is derived using Eq. (1) in Lützgendorf et al (2011) and results in σ e = (13.4 ± 0.2) km s −1 . This is in very good agreement with the central velocity dispersion σ c = (13.4 ± 2.6) km s −1 of Pryor & Meylan (1993).…”
Section: Inner Velocity-dispersion Profilementioning
confidence: 59%
See 1 more Smart Citation
“…The effective velocity dispersion is derived using Eq. (1) in Lützgendorf et al (2011) and results in σ e = (13.4 ± 0.2) km s −1 . This is in very good agreement with the central velocity dispersion σ c = (13.4 ± 2.6) km s −1 of Pryor & Meylan (1993).…”
Section: Inner Velocity-dispersion Profilementioning
confidence: 59%
“…However, recent observations (e.g. Gebhardt et al 2000;Gerssen et al 2002;Gebhardt et al 2005;Noyola et al 2008;Lützgendorf et al 2011) have shown that the velocity-dispersion profiles of some globular clusters and dwarf galaxies are consistent with hosting a massive black hole at their center.…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that simulations specifically designed to match particular cases are needed to fur-ther understand in details the discrepancies reported in the literature (e.g. see the case of NGC 6388, Lützgendorf et al 2011Lützgendorf et al , 2015Lanzoni et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, integrated light spectroscopy seems to measure rising central velocity dispersions, favouring the presence of IMBHs (see e.g., Noyola et al 2010 for ω Cen; Lützgendorf et al 2011Lützgendorf et al , 2015 for NGC 6388), while resolved stellar kinematics do not confirm the presence of this signature (see van der Marel & Anderson 2010 for proper motion measurements of ω Cen; Lanzoni et al 2013 for individual line-of-sight measurements in NGC 6388).…”
Section: Introductionmentioning
confidence: 99%
“…Internal rotation may also play an indirect role in the open question of whether there are intermediate-mass black holes (IMBH) in some GCs. In fact, the detection of strong gradients in the velocity dispersion profile toward the cluster core is often interpreted as a hint of the presence of an IMBH (Baumgardt et al 2005), but the evidence gathered so far in support of the existence of IMBHs is inconclusive and controversial, and none of the published studies (van der Marel & Anderson 2010;Lützgendorf et al 2011;Lanzoni et al 2013) did consider differential rotation, which, together with anisotropy, can yield gradients in the velocity dispersion profiles Bianchini et al 2013). Finally, recent investigations indicate that rotation could be a key ingredient in the formation of multiple generations of stars in GCs (Bekki 2010;Mastrobuono-Battisti & Perets 2013).…”
Section: Introductionmentioning
confidence: 99%